Kite Partnership Hot Grillicious Sauce - Abdul Rasib, Ahmad Shahril Khusairi; Othman, Mohamad Faiz; Ghafar, Rozita; Mohd Noor, Nurul Farhana; Mohd Zamri, Nur Nadiah Atiqah (2014)
KITE Partnership I is a Small Medium Enterprise (SME) in Malaysia specializing in producing and selling familiar Malaysian sauces of high quality. The company is structured as a partnership with five members. The general manager contributes RM 192,000, while the other four members contribute RM 12,000 each to the capital. The company's rationale for producing sauce is to enhance the flavor of food, meet customer demand and needs, and ensure maximum customer satisfaction. KITE Partnership is committed to producing the best quality sauce to make customers not only enjoy the product but love it, aiming for an increase in demand over time. A key objective is to achieve maximum profit and build a successful company within a short period. In the near future (within two years or more), the company hopes to establish and expand widely throughout the country, with the target of making their product, Hot Grillicious sauce, a favourite in Malaysia.